The effect of contextual interference on motor learning among healthy adolescents: a systematic review - Wang, Xiaopeng; Abdullah, Borhannudin; Samsudin, Shamsulariffin (ASR Research Center, 2022)
During the beginning of the 1990s, experimental research on the effect of contextual interference was widely carried out, which also brought significant of research profit. Considerable laboratory experiments supported the contextual interference-effect. However, the utility of laboratory-based research has been questioned, and no consistent conclusions were yielded in actual motor learning practices. This review aims to determine the effect of contextual interference (low, moderate, and high level) on actual motor learning under non-laboratory experiments among healthy adolescents. Four academic databases (Web of Science, PubMed, Scopus, and SPORT Discus) were searched systematically with predefined search terms. We selected studies through PICOS and conducted a systematic literature review according to the PRISMA guidelines. Thirteen studies were included, of which 12 were at low risk of bias, while only one was classified as high risk. In general, experience in participants has been shown to improve the contextual interference effect, and limited evidence was presented regarding their age. Results on experimental types (laboratory or non-laboratory) are mixed. Task variations from the different motor programs did not show an effect among children, probably because the task variations were too difficult and exceeded their ability. There is a limitation of high-quality evidence about the contextual interference effect on healthy adolescents under different practices schedules. The results are mainly inconsistent; several studies showed the CI effect, but this cannot be applied to the entire field of motor learning. Further independent studies of the parameters influencing the CI effect are required in future research.